Democracy and Socialism - Gasiūnas, Adolfas (Problemos, 1974)
The paper examines the historical conditionality of the principle of democracy, its new content under socialism. Capitalist relations of production stipulate the fact that the principle of democracy in the bourgeois society has a purely formal content – equality of citizens with respect to them. On the basis of idealistic social methodology this political equality acquires not only the meaning of human emancipation proper but that of a social ideal as well. Marxism has proved that human emancipation is an economical phenomenon in its content related to the overcoming of the estrangement of social phenomena, i.e., the class structure of society. This task is solved under socialism by means of political-legal institutions. Consequently, democracy as a form of the political-legal organisation of society appears under socialism not as a social ideal but as the objectively necessary political form for the construction of classless society. At the same time democracy gains new content linked with realization of genuine equality of members of society. This process develops under socialism as socialism creates the material prerequisites for the communist society.